2016
DOI: 10.1038/srep37171
|View full text |Cite
|
Sign up to set email alerts
|

Loss of NMDA receptors in dopamine neurons leads to the development of affective disorder-like symptoms in mice

Abstract: The role of changes in dopamine neuronal activity during the development of symptoms in affective disorders remains controversial. Here, we show that inactivation of NMDA receptors on dopaminergic neurons in adult mice led to the development of affective disorder-like symptoms. The loss of NMDA receptors altered activity and caused complete NMDA-insensitivity in dopamine-like neurons. Mutant mice exhibited increased immobility in the forced swim test and a decrease in social interactions. Mutation also led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 49 publications
1
20
0
2
Order By: Relevance
“…Consistent with this finding, we recently reported that the induction of the mutation in the NR1 DATCreERT2 mice causes a complete loss of NMDA receptor-dependent bursting of midbrain DA neurons (Jastrzębska et al, 2016). Considering the role of DA neuron burst firing in reward prediction error coding (Schultz et al, 1997; Glimcher, 2011), the observed effects of the mutation are to an extent unexpected, as no significant changes in learning rates were observed.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Consistent with this finding, we recently reported that the induction of the mutation in the NR1 DATCreERT2 mice causes a complete loss of NMDA receptor-dependent bursting of midbrain DA neurons (Jastrzębska et al, 2016). Considering the role of DA neuron burst firing in reward prediction error coding (Schultz et al, 1997; Glimcher, 2011), the observed effects of the mutation are to an extent unexpected, as no significant changes in learning rates were observed.…”
Section: Discussionsupporting
confidence: 69%
“…The following three strains of genetically modified mice were used in the study: NR1 DATCreERT2 mice, which had an inducible deletion of the NR1 subunit of the NMDA receptor in DA transporter (DAT)-expressing neurons (Engblom et al, 2008; Jastrzębska et al, 2016); NR1 D1CreERT2 animals, which had an inducible loss of the NR1 subunit of the NMDA receptor in D 1 receptor-expressing neurons (Sikora et al, 2016); and mGluR5 KD-D1 mice, which had a selective knockdown of the mGluR5 receptor in D 1 -expressing neurons (Novak et al, 2010; Rodriguez Parkitna et al, 2013). All strains were bred to be congenic with the C57BL/6N strain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specifically cholinergic molecular loss of function in STs [137] points strongly to the fact that cholinergic systems support anti-distractive cognitive control, whilst also allowing for attentive shifts with reorientation to cues and cue-re-sponsive action [113], like approaching the goal! Present psychological research on humans applies the concept of "ST-to-GT" [107] and could use cross-validating tests for "UC-to-CO" [1,46], while studying resistance to temptation or effort [106] would also test the here exposed hypothesis of homology.…”
Section: Biopersonology and Dyn4-tammentioning
confidence: 99%
“…TGFβ- [111] or NMDAR- [112] activity on striatal DA-neurons. The lack of the latter glutamatergic input slows down learning, social contacts and forced swimming, but not effortful performance [113].…”
Section: Habits Are Not Always Rapid or The Primary Issuementioning
confidence: 99%